(untitled) (Phnom Penh, 1997)
Presentation of the result of experiments aimed at improving the sustainability of livestock base farming systems in the participating countries of the FAO project,..
Keywords: Agricultural systems,Hệ thống nông nghiệp; Southeast Asia,Đông Nam Á